Key performance indicators for Australian mental health court liaison services - Davidson, F.; Heffernan, E.; Greenberg, D.; Butler, Tony; Burgess, P. (2017)
© 2017, © The Royal Australian and New Zealand College of Psychiatrists 2017. Objectives: The aim of this paper is to describe the development and technical specifications of a framework and national key performance indicators (KPIs) for Australian mental health Court Liaison Services (CLSs) by the National Mental Health Court Liaison Performance Working Group (Working Group). Methods: Representatives from each Australian State and Territory were invited to form a Working Group. Through a series of national workshops and meetings, a framework and set of performance indicators were developed using a review of literature and expert opinion. Results: A total of six KPIs for CLSs have been identified and a set of technical specifications have been formed. Conclusions: This paper describes the process and outcomes of a national collaboration to develop a framework and KPIs. The measures have been developed to support future benchmarking activities and to assist services to identify best practice in this area of mental health service delivery.